2020
DOI: 10.3390/coatings10100982
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Superhydrophobic Aluminum Surfaces with Anti-Biofouling and Antibacterial Properties

Abstract: Surfaces in a hygiene critical environment can become potential reservoirs for transmission of pathogenic infections. Engineering surfaces with the tunable anti-biofouling and antibacterial properties could reduce infections particularly in hospitals and public transport hubs. In the present work, a facile two-step process has been deployed to fabricate a superhydrophobic and antibacterial aluminum surface by chemical etching, followed by passivation with low surface energy octyltriethoxysilane (OTES) molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…They demonstrated that durable antibacterial superhydrophobic fabric showed widely application prospects in self‐cleaning and antibacterial clothing. Agbe and Sarkar [ 124 ] fabricated antibacterial superhydrophobic coatings by chemical etching and modification with low surface energy octyltriethoxysilane molecules. The wettability and antibacterial properties were monotonically tuned by adding quaternary ammonium molecules.…”
Section: Qacs‐based Antibacterial Superhydrophobic Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that durable antibacterial superhydrophobic fabric showed widely application prospects in self‐cleaning and antibacterial clothing. Agbe and Sarkar [ 124 ] fabricated antibacterial superhydrophobic coatings by chemical etching and modification with low surface energy octyltriethoxysilane molecules. The wettability and antibacterial properties were monotonically tuned by adding quaternary ammonium molecules.…”
Section: Qacs‐based Antibacterial Superhydrophobic Coatingsmentioning
confidence: 99%
“…It was considered that the F/Q-MSNs cotton fabrics were prospective for Reproduced with permission. [124] Copyright 2020, MDPI.…”
Section: Qacs-based Antibacterial Superhydrophobic Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] Another strategy consists in applying specic coatings to acquire antibacterial surface properties (superhydrophobicity, nanostructuring) or to incorporate into the material a wide variety of known antibacterial compounds (copper, silver, quaternary ammoniums compounds (QACs), etc.). 10,12,[22][23][24][25][26][27][28] QACs are antimicrobial agents effective against a broad spectrum of Gram-positive and Gram-negative bacteria as well as several enveloped viruses, and they are widely used in cleaning products. 29,30 The persistence of their antibacterial property over time and over a wide pH range, their odorless and amphiphilic properties, as well as the low cost of commercial grade QACs make them very good candidates for manufacturing biocidal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the unique water repelling nature of lotus leaves, superhydrophobic surfaces have been extensively explored for various potential applications, such as anti-fogging, antiicing, anti-corrosion, oil/water separation, self-cleaning and anti-contamination, etc. [1][2][3][4][5][6][7]. Superhydrophobic surface has a water contact angle (WCA) higher than 150 • and a water rolling angle less than 10 • .…”
Section: Introductionmentioning
confidence: 99%